Lyophyllum pallidofumosum sp. nov. (Lyophyllaceae, Agaricales), from southwestern China - Ma, Yuanhao; Liu, Ping; Zhao, Ziyue; Chen, Weimin; Zhao, Yongchang (Phytotaxa, 2022)
We describe a new species of Lyophyllum based on the morphology and molecular phylogenetic analyses. The species is widely distributed above ca. 2000 m in mixed forests dominated by Pinus yunnanensis, Pinus armandi, and Quercus fabrei in Yunnan Province. It can be distinguished by its greyish orange pileus surface, margin with waves when old; globose to subglobose spores (4.5–5.6 × 4.3–5.4 µm), clavate basidia (25–34 × 7–9 µm). Moreover, the growth rate of cultured mycelia of the species in the YPD medium is higher than that of L. decastes complex species under the same conditions. Phylogenetic analyses based on the internal transcribed spacer (ITS) and large ribosomal subunit (LSU) regions of the nuclear ribosomal DNA (nrDNA) indicated that L. pallidofumosum is a distinct taxon closely related to L. fumosum and L. shimeji.